PENGARUH PRICE DISCOUNT DAN BONUS PACK TERHADAP KEPUTUSAN IMPULSE BUYING PADA KONSUMEN GALERI BATIK DI SAMPIT - Ahmad Rudini (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research uses accidental sampling technique. And the data is tested using validity test, reliability test, hypothesis testing and research data analysis using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis and analysis of determination. Based on the results of hypothesis testing in this study, the t-test for the price discount variable (X1) is tcount > ttable (5.376 > 2.01174) and the significant level is 0.000 <0.05, then H0 is rejected and Ha is accepted. This means that there is a significant influence between the price discount on impulse buying decisions. Meanwhile, for the t-test for the bonus pack variable (X2), namely tcount > ttable (3.752 > 2.01174) and a significant level of 0.000 <0.05, H0 is rejected and Ha is accepted, meaning that there is a significant influence between the bonus pack on impulse buying decisions. Then for the f-test, namely fcount > ftable (26.945 > 3.20) and a significant level of 0.000 <0.05, meaning that simultaneously price discount and bonus packs on impulse buying decisions for Batik Gallery consumers in Sampit. The number r of 0.731 shows the relationship/correlation between impulse buying decisions on consumers of Batik Gallery in Sampit and the independent variable is strong. The R square value of 0.534 means that 53.4% ​​of the impulse buying decision variables to consumers (Y) can be explained by the price discount variable (X1) and the bonus pack (X2). While the remaining 46.6% is influenced by other variables such as price, product quality, location and so on. Based on the results of the multiple linear regression test, the equation Y = 1.679 + 0.728 (X1) + 0.445 (X2) means the score / constant value (α) indicates if there is no increase in the price discount and bonus pack variables, the value of the impulse buying decision is 1.679. And each addition of one score/value of the price discount variable gives an increase of 0.728 on impulse buying decisions with the condition that X2 remains and each addition of one score/value of the bonus pack variable gives the same increase of 0.445 on impulse buying decisions with fixed X1.